Production Planning and Control at PT XYZ Using Manufacturing Resources Planning Method - Wijaya, Cindy; Loren, Jesica; Tampubolon, Jusra (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2021)
PT.XYZ is an industrial manufacturing company which produces egg trays. The problems being faced by this company is that since it started operating, it never applied a system in production planning and controlling which now causes many problems. This resulted in the production cost increasing rapidly. Therefore in this study, the researchers conducted a research to solve and prevent the problems from resurfacing again. The method chosen by the researchers is Manufacturing Resources Planning, for this method is very complexed and detailed, therefore, more aspects will be covered. This method is also expected to help the company in the future.